AI-Based Interactive Media Creation Training Using Curipod for High School Teachers: Strengthening Digital Literacy - Hani Sulsilah; Ernita Susanti; Rahmat Rizal; Ifa Rifatul Mahmudah (Fakultas Keguruan dan Ilmu Pendidikan-Universitas Timor, 2025)
The lack of a real-time feedback mechanism in the learning process can lead to undetected misconceptions, delayed reflection, and decreased student participation. This community engagement program is implemented to enrich AI-based interactive learning by utilizing Curipod as a real-time feedback platform, facilitating students' understanding and periodic evaluation. The intervention involved nine teachers (n=9) from multiple subject areas at a public senior high school in Pangandaran Regency, Indonesia. The program comprised three phases: 1) pre-activity, 2) training, and 3) monitoring and evaluation. The training followed a three-step sequence: presentation, live demonstration, and assistance. Evaluation included on-site observation during the training, a post-training test, and the interaction rate during the training. The results showed that the average test achievement reached 94,4% with a “very good” category, while the interaction level during the training reached 95%. Participants provided positive responses toward the activity, and eight out of nine participants have implemented Curipod in their classroom learning. Overall, the program was successful and made a tangible contribution to active learning practices. Overall, the program was successful and made a tangible contribution to active learning practices; eight of nine teachers subsequently integrated Curipod into their classroom instruction.